2018
DOI: 10.5395/rde.2018.43.e27
|View full text |Cite
|
Sign up to set email alerts
|

Light transmittance of CAD/CAM ceramics with different shades and thicknesses and microhardness of the underlying light-cured resin cement

Abstract: ObjectivesThe aim of this in vitro study was to evaluate the effects of the thickness and shade of 3 types of computer-aided design/computer-aided manufacturing (CAD/CAM) materials.Materials and MethodsA total of 120 specimens of 2 shades (A1 and A3) and 2 thicknesses (1 and 2 mm) were fabricated using VITA Mark II (VM; VITA Zahnfabrik), IPS e.max CAD (IE; IvoclarVivadent), and VITA Suprinity (VS; VITA Zahnfabrik) (n = 10 per subgroup). The amount of light transmission through the ceramic specimens was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…This increases the number of encounters between the light beam and the crystal boundaries, resulting in higher scattering and, thus, lower light transmission 14,15 . Similar to a previous study, more light was transmitted through the feldspathic ceramic than all other ceramics, especially through 1.5 and 2.0 mm 17 . The needle‐shaped lithium disilicate and lithium silicate crystals 26,27 may cause more light scattering compared to feldspathic ceramic, which has lower crystalline content 26 .…”
Section: Discussionsupporting
confidence: 64%
“…This increases the number of encounters between the light beam and the crystal boundaries, resulting in higher scattering and, thus, lower light transmission 14,15 . Similar to a previous study, more light was transmitted through the feldspathic ceramic than all other ceramics, especially through 1.5 and 2.0 mm 17 . The needle‐shaped lithium disilicate and lithium silicate crystals 26,27 may cause more light scattering compared to feldspathic ceramic, which has lower crystalline content 26 .…”
Section: Discussionsupporting
confidence: 64%
“…This result can be attributed to the amount of light passing through ceramic materials. Previous studies have shown that the light intensity weakens with the increasing ceramic layer thickness [43, 44] even if the ceramics are selected as highly translucent [15]. Considering the results of the current study, it can be speculated that higher bond strength values are achievable with reduced ceramic thickness.…”
Section: Discussionmentioning
confidence: 48%
“…Glass matrix ceramics (GMCs) are preferred when the main goals are esthetic results and stable micro-mechanical and chemical adhesive interaction with composite resin luting materials [3][4][5][6] . Among GMCs lithium disilicate (LDS) based ceramics have gained popularity recently, due mainly to their versatility, with an indication range that goes from veneers to three-piece bridges in premolar areas and implant-supported single crowns 7,8 . LDS restorations can be made either by traditional heat-pressing procedure or through a digital workflow and milling process (CAD-CAM).…”
Section: Introductionmentioning
confidence: 99%
“…LDS restorations can be made either by traditional heat-pressing procedure or through a digital workflow and milling process (CAD-CAM). There are key differences in crystal distribution, shape and size between pressed and CAD-CAM restorations, all of which are prone to affect the transmittance of the structure 8,9 . One of the most important factors related to clinical success of glass ceramics is the achievement of durable bonding between dental tissues and the restorative unit through a composite-based luting material (CBLM) of adequate mechanical properties 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation